Field evaluation of Hevea brasiliensis clones for the incidence of white root disease in Nigeria - Akpaja, Emmanuel O.; Ogbebor, Nicholas O. (Journal of Plantation Crops, 2021)
Incidence and severity of white root disease affecting rubber trees were determined in ûve rubber clones of 10 and 35 years old. The percentage of infection, aggregate failure, level of infectivity and gross economic loss were evaluated. There were variations in resistance to white root disease among rubber clones studied. However, no rubber clone was free from this disease even though there were signiûcant (P>0.05) differences in the ability of the pathogen to attack different clones. Results of disease index in the multiclonal plot were compared with those from plots of specific clones of rubber. Percentage infection in 35-year-old rubber plots was signiûcantly (P>0.05) higher than 10-year-old rubber trees. The level of infectivity of white root disease pathogen was generally high with the lowest value for missing stands of 3.33 ± 1.67 (representing 41.63 per cent of expected neighbouring stands) and as many as 6.00 ± 0.56 (representing 75 per cent of expected neighbouring stands) in 10 and 35-year-old rubber plots, respectively. The estimated gross economic losses (N 113,652.30 to 274,734.30) per year recorded in the study were high. This study indicates the need for regular monitoring of white root disease in rubber plantations so that the disease can be managed and controlled at an early stage of the disease occurrence.